2018
DOI: 10.1007/s11136-018-1943-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical, sensory, and cognitive functioning among centenarians: a comparison between the Tokyo and Georgia centenarian studies

Abstract: Functional differences may be due, in part, to different care patterns for the oldest old in the United States when compared to Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
1
18
1
Order By: Relevance
“…Our centenarians showed better ADL independence than those in Australia (Richmond et al, 2011), U.S. (Jopp et al, 2016), and Japan (Arai et al, 2014). Walking has been consistently reported as the most impaired item: 66.7% in the Georgia Centenarian Study and 78.0% in the Tokyo Centenarian Study (Martin et al, 2018), but only 33.8% in our study.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Our centenarians showed better ADL independence than those in Australia (Richmond et al, 2011), U.S. (Jopp et al, 2016), and Japan (Arai et al, 2014). Walking has been consistently reported as the most impaired item: 66.7% in the Georgia Centenarian Study and 78.0% in the Tokyo Centenarian Study (Martin et al, 2018), but only 33.8% in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…Bathing was another top-ranking difficult task in the Fordham (Jopp et al, 2016) and Tokyo centenarian studies (Martin et al, 2018), but 71.1% of our centenarians were independent. In contrast, transportation is the most impaired activity among our centenarians, similar to Japan and U.S. centenarians (Martin et al, 2018). Together, these findings support the variations in ADL independence among centenarians by countries.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In the present study it was found that the dependence for the BADLs is different in older adults with and without alteration of visual acuity, a finding which is consistent with an article on a Mexican population (3) . This is consistent in populations of foreign countries; in Tokyo and Georgia, a study was carried out to find out the predictors of dependency and it was found that vision predicts in up to 60% the alteration in functionality (26) , this is why the evaluation of visual acuity must be present in the medical evaluations that are carried out on older adults to correct the alteration as much as possible and avoid dependencies due to this cause. Likewise, it was observed that the dependence for the BADLs and the IADLs is different in the subjects with and without alteration of the tactile acuity in the feet, this takes coherence since both activities include performing displacement actions (gait, climbing stairs)…”
Section: Discussionmentioning
confidence: 68%